Implementation of 2030 Free From HIV/AIDS Policy in Papua According to Van Metter and Van Horn Model: A Systematic Review - Sukatemin Sukatemin; Edison Kabak; Syaifoel Hardy (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The 2030 free from HIV/AIDS program is needed to clarify the direction of achieving its goals. The research objective is to examine the existing policy measures in Papua in particular and Indonesia in general. This study used a systematic review method. Data was filtered from Google search engine, with keywords: HIV/AIDS, Papua, and Van Metter and Van Horn Model. Documents were screened from Google Scholar, PubMed, Semantic Scholar, and ResearchGate for the last 5 years (2016-2022) and government official documents, in Indonesian or English. The PRISMA diagram was used that include identification, Screening, Eligibility, and Included. The data were processed according to the Van Metter and Van Horn Model which includes 6 aspects: standards, policy sources, communication between organizations, characteristics of implementing agencies, environment, and performance. The 13 journals identified in the Included category show that HIV/AIDS is still major problem (journals no.1 to 13). The policy problems exist due to lack of the aspects of leadership and governance (n=2), facilities and facilities (n=2), communication (n=7), the willingness of implementing institutions (n=5), environmental issues (n=7) and performance problems (n=11). Meanwhile, the prioritized three  problems were communication (n=7), environment (n=7), and performance (n=11) of the total journals in the Included category studied (n=13). Out of six policy aspects according to Van Metter and Van Horn model, 33% is problematic. The findings suggest more concrete steps on communication, environment and work performance to be needed in the implementation of 2030 free from HIV/AIDS program.  Abstrak: Program bebas HIV/AIDS tahun 2030 diperlukan untuk memperjelas arah pencapaian tujuannya. Tujuan penelitian adalah untuk mengkaji langkah-langkah kebijakan yang ada di Papua pada khususnya dan Indonesia pada umumnya. Penelitian ini menggunakan metode tinjauan sistematis. Data disaring dari mesin pencari Google, dengan kata kunci: HIV/AIDS, Papua, dan Model Van Metter dan Van Horn. Dokumen disaring dari Google Scholar, PubMed, Semantic Scholar, dan ResearchGate selama 5 tahun terakhir (2016-2022) dan dokumen resmi pemerintah, dalam bahasa Indonesia atau bahasa Inggris. Diagram PRISMA digunakan yang meliputi identifikasi, penyaringan, kelayakan, dan inklusi. Data diolah menurut Model Van Metter dan Van Horn yang mencakup 6 aspek: standar, sumber kebijakan, komunikasi antar organisasi, karakteristik lembaga pelaksana, lingkungan, dan kinerja. Dari 13 jurnal yang teridentifikasi dalam kategori Included menunjukkan bahwa HIV/AIDS masih menjadi masalah utama (jurnal no. 1 sampai 13). Masalah kebijakan terjadi karena kurangnya aspek kepemimpinan dan tata kelola (n=2), sarana dan prasarana (n=2), komunikasi (n=7), kemauan lembaga pelaksana (n=5), masalah lingkungan ( n=7) dan masalah kinerja (n=11). Sementara itu, tiga masalah yang diprioritaskan adalah komunikasi (n=7), lingkungan (n=7), dan kinerja (n=11) dari total jurnal yang termasuk dalam kategori yang diteliti (n=13). Dari enam aspek kebijakan menurut model Van Metter dan Van Horn, 33% bermasalah. Temuan penelitian ini menunjukkan langkah-langkah yang lebih konkrit pada komunikasi, lingkungan dan kinerja yang diperlukan dalam pelaksanaan program bebas dari HIV/AIDS tahun 2030